A method to minimize the workpiece deformation using a concept of intelligent fixture. (December 2017) - Gonzalo, Oscar; Seara, Jose Mari; Guruceta, Enrique; Izpizua, Alberto; Esparta, Mikel; Zamakona, Iker; Uterga, Nicolas; Aranburu, Axier; Thoelen, Johannes
Abstract: Manufacturing processes are commonly affected by the low stiffness of the components limiting the quality and precision of the final product. Precision is one of the most important issues in the machining process, and the main cause for rejection is the part static deformation and the dynamic vibrations. The static deformation is mainly affected by two factors: deformation due to clamping and process forces, and geometrical distortions due to material removal and residual stress relieving during processing. The deformations caused by the clamping in the fixture are normally associated to existing distortion in the raw workpiece due to previous manufacturing processes and to the clamping forces. These problems lead to uncertainties in the set-up process, hindering the fixture functions, the achievement of a right positioning of the workpiece and the avoidance of deformations due to clamping forces. This paper presents an analysis to identify the causes of the static deformations during clamping and a method to correct the geometrical distortion and deformation of a clamped workpiece by the evaluation of the reaction forces in the selected relevant clamping points. It covers the design and validation of an active clamping unit to minimize the deformation produced by the fixture that could affect the machining process. The developed clamping unit presents an alternative to combine the locator and the clamper in a single component that controls the reaction force and the deformation of the workpiece in the clamping point, and it performs the positioning of that point to minimize the distortion of the workpiece. The clamping unit was verified in laboratory conditions and then tested in an industrial application, evaluating the capabilities related to positioning and reaction force control. Highlights: A method to correct the deformation associated to overclamped workpieces. An intelligent clamping unit to correct the position of the claws. Close loop control of the position and the reaction force. Precise repositioning (±0.01 mm) and stress free clamping.